2009
DOI: 10.1080/09537100902849836
|View full text |Cite
|
Sign up to set email alerts
|

Platelets arachidonic acid metabolism in patients with essential hypertension

Abstract: Arachidonic acid's (AA) metabolites, eicosanoids, exert a tremendous influence on circulatory and vascular homeostasis, and in humans are generated by many organs and cell types. In this study we wanted to verify whether platelets AA metabolism play a significant role in pathogenesis of essential hypertension (EH). Participants were divided into the study (EH) and the control group. Plasma and urine concentrations of isoprostanes (8-iPF(2alpha)-III) and thromboxane B(2) (TxB(2)) were determined using the ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 27 publications
2
23
0
1
Order By: Relevance
“…Besides NAD(P)H oxidase, mitochondria and COX-1, other molecules are likely to be involved in ROS generation, such as 12lipoxygenase, cPLA 2 and PKC. Recently, it was reported that platelet AA metabolism exerts a proatherosclerotic effect [38]. In our study, PLA 2 and 12-lipoxygenase protein expressions were found to be increased in the platelets isolated from the HH group, confirming the contribution of these molecules to ROS generation in combined hypertension-hypercholesterolemia.…”
Section: Discussionsupporting
confidence: 81%
“…Besides NAD(P)H oxidase, mitochondria and COX-1, other molecules are likely to be involved in ROS generation, such as 12lipoxygenase, cPLA 2 and PKC. Recently, it was reported that platelet AA metabolism exerts a proatherosclerotic effect [38]. In our study, PLA 2 and 12-lipoxygenase protein expressions were found to be increased in the platelets isolated from the HH group, confirming the contribution of these molecules to ROS generation in combined hypertension-hypercholesterolemia.…”
Section: Discussionsupporting
confidence: 81%
“…In human umbilical artery smooth muscle cells, 11-HETE inhibited vascular smooth muscle cell proliferation [54], whereas in the isolated Guinea Pig lungs, 5- and 15-HETEs produced vasoconstriction and edema [55]. Also, the generation of mid-chain HETEs is increased in essential hypertension [56] suggesting that they could be involved in its pathogenesis. These reports point to opposite effects of EETs and HETEs in vascular biology.…”
Section: Discussionmentioning
confidence: 99%
“…Results of other studies also showed that the major source of endogenously derived AA are platelets and that translocation of cPLA 2 from the cytosol to the membrane releases AA from membrane phospholipids, [57] and produces (AE)-12-HETE and TXB 2 as major metabolites. [58,59] The results of this study show increased production of (AE)-9-HETE, (AE)-12-HETE, (AE)-15-HETE, LTB 4 , LTE 4 and TXB 2 in CI A23187-treated equine whole blood which could have been formed from platelets containing endogenous source of AA. Pretreatment of equine whole blood with DEX, an inducer of a protein which inhibits cPLA 2 , resulted in a significant reduction in all HETEs, LTs and TBX synthesis.…”
Section: Accuracy and Precisionmentioning
confidence: 80%